2008
DOI: 10.1177/0886260507313532
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Empathy in Neglectful Mothers and Mothers at High Risk for Child Physical Abuse

Abstract: This study investigates whether mothers who are neglectful and at high risk for child physical abuse present a deficit in empathy. Participants were neglectful mothers (n=37), mothers at high risk for child physical abuse (n=22), and nonmaltreating mothers (n=37). The Interpersonal Reactivity Index, a self-report measure assessing specific dimensions of empathy, was used to assess dispositional empathy. No differences between neglectful and non-neglectful mothers were found for perspective taking, empathic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…The patient, sensing the caregiver’s stress, responds in a similar fashion by distancing from the caregiver (Austin et al, ). Research has shown, although not in the medical field, that parents with higher levels of personal distress engage in more negative verbal and expressive behavior toward their children (Valiente et al, ) and are also more likely to physically abuse their children (De Paúl, Pérez‐Albéniz, Guibert, Asla, & Ormaechea, ). These findings might apply to the patient–caregiver context in some instances (McMahon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The patient, sensing the caregiver’s stress, responds in a similar fashion by distancing from the caregiver (Austin et al, ). Research has shown, although not in the medical field, that parents with higher levels of personal distress engage in more negative verbal and expressive behavior toward their children (Valiente et al, ) and are also more likely to physically abuse their children (De Paúl, Pérez‐Albéniz, Guibert, Asla, & Ormaechea, ). These findings might apply to the patient–caregiver context in some instances (McMahon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence has begun to show difficulties in CPS parents’ encoding of social information (Azar, Read, Biancaniello, Callen, & Martinez, 2011; Azar, Read, Proctor, & Arnett, 2011; Azar, Robinson, Hekimian, & Twentyman, 1984; Hildyard & Wolfe, 2007), identifying and solving childrearing problems and cognitive flexibility (Azar, Read, & Proctor, 2009; Azar, et al, 1984; De Paul, Perez-Albeniz, Guibert, Asia, & Ormaechea, 2008), and mis-appraising their children's behavior (Bugental & Happaney, 2004; Larrance & Twentyman, 1983). SIP difficulties have also been found to characterize some individuals with intellectual disabilities, but have been shown to predict maltreatment over and above IQ scores (Azar, et al, 2012b).…”
Section: Social Information Processing and Neurocognitive Factors Andmentioning
confidence: 99%
“…Hipotetiza-se que o estado de angús-tia seria um dos fatores responsáveis pela dificuldade em se colocar na perspectiva do outro, principalmente em situações em que estaria em questão a expressão de sentimentos de sofrimento. Segundo o modelo do PIS, tal dificuldade influenciaria a avaliação e a interpretação do comportamento do outro (De Paúl, Pérez-Albéniz, Guibert, Asla, & Ormaechea, 2008;Francis & Wolfe, 2008).…”
unclassified